Interleukin-6 in Schizophrenia—Is There a Therapeutic Relevance? - Borovcanin, Milica Milovan; Jovanovic, Ivan; Radosavljevic, Gordana; Pantic, Jelena; Minic Janicijevic, Slavica; Arsenijevic, Nebojsa; Lukic, Miodrag L. (Frontiers in Psychiatry, 2017)
Renewing interest in immune aspects of schizophrenia and new findings about the brain-fat axis encourages us to discuss the possible role of Interleukin-6 (IL-6) in schizophrenia. Previously, it was suggested that a primary alteration of the innate immune system may be relevant in schizophrenia. Functional dichotomy of IL-6 suggests that this chemical messenger may be responsible for regulating the balance between pro- and anti-inflammatory responses, with tissue specific properties at the periphery and in the central nervous system. Specific phase of this chronic and deteriorating disorder must be considered, which can involve IL-6 in acute or possible chronic inflammation and/or autoimmunity. We give an overview of IL-6 role in the onset and progression of this disorder, also considering cognitive impairment and metabolic changes in patients with schizophrenia. Data suggest that decreased serum level of IL-6 following antipsychotic therapy could be predisposing factor for the development of obesity and obesity related metabolic disorders in schizophrenia. As we reviewed, the IL-6 plays significant role in disease genesis and progression, so the use of specific inhibitors may not only have beneficial effects with respect to exacerbation and positive symptoms severity, but can may attenuate cognitive impairment in patients with schizophrenia.